2014
DOI: 10.1371/journal.pone.0088804
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-Seq Analysis of Transcriptome and Glucosinolate Metabolism in Seeds and Sprouts of Broccoli (Brassica oleracea var. italic)

Abstract: BackgroundBroccoli (Brassica oleracea var. italica), a member of Cruciferae, is an important vegetable containing high concentration of various nutritive and functional molecules especially the anticarcinogenic glucosinolates. The sprouts of broccoli contain 10–100 times higher level of glucoraphanin, the main contributor of the anticarcinogenesis, than the edible florets. Despite the broccoli sprouts’ functional importance, currently available genetic and genomic tools for their studies are very limited, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 88 publications
2
36
0
1
Order By: Relevance
“…The cDNA library was sequenced on the Illumina sequencing platform (Illumina HiSeq™ 2000, Illumina, San Diego, CA, USA) using the single-end paired-end technology in a single run. The original image processes of sequencing, base-calling, and quality value calculation were performed by the Illumina GA Pipeline (version 1.6, Illumina, San Diego, CA, USA), in which 90-bp paired-end reads were obtained [20,21]. …”
Section: Methodsmentioning
confidence: 99%
“…The cDNA library was sequenced on the Illumina sequencing platform (Illumina HiSeq™ 2000, Illumina, San Diego, CA, USA) using the single-end paired-end technology in a single run. The original image processes of sequencing, base-calling, and quality value calculation were performed by the Illumina GA Pipeline (version 1.6, Illumina, San Diego, CA, USA), in which 90-bp paired-end reads were obtained [20,21]. …”
Section: Methodsmentioning
confidence: 99%
“…For example, small RNA-Seq has revealed DEGs in the early development of broccoli pollen [19], and transcriptome analyses have been used to examine four transcription factors in normal and abortive buds of an Ogura-CMS line and its maintainer line [12]. In addition, the roles of pigment mechanisms in post-harvest broccoli yellowing [20], gene expression patterns associated with sulforaphane metabolism in broccoli orets [21], glucosinolate metabolism in seeds and sprouts [22,23], and yield heterosis in curds of broccoli have also been elucidated by RNA-Seq technology [24]. To the best of our knowledge, it would be the rst report of comparative transcriptome analyses of isogenic Ogura-CMS, DGMS and inbred lines in broccoli orets.…”
Section: Introductionmentioning
confidence: 99%
“…italica Planch.) seed germination, Gao et al (2014) [11] identified 25 putative glucosinolate metabolism-related genes, which shared 62.04%-89.72% nucleotide sequence identity with the Arabidopsis orthologs. In particular, the expression level of myrosinase TGG2 after germination was 20-130 times greater than in dry seeds.…”
Section: Introductionmentioning
confidence: 99%